Pengaruh lingkungan kerja dan komitmen keorganisasian pegawai terhadap kinerja pegawai pada Kantor Camat Mestong Kabupaten Muaro Jambi - Indah Dwi Agusti; Edward Edward; Rts Ratnawati (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to determine the effect of the work environment and organizational commitment on employee performance. The type of this research is 40 employees of the Mestong District Office, Muaro Jambi Regency. Methods of data collection using questionnaires and measured by Likert scale. Data testing techniques used in this study include instrument testing (validity test, reliability test), multiple linear regression analysis t test, F test and coefficient of determination test (R2) with the help of SPSS application. The findings of this study partially show that the work environment has a positive and significant effect on employee performance and organizational commitment has a positive and significant effect on employee performance. Simultaneously the work environment and organizational commitment have a positive and significant effect on the performance of the Mestong District Office employees, Muaro Jambi Regency